## Solving for a, b, and c in (x+3)(x+4)=0

The equation (x+3)(x+4)=0 represents a quadratic equation in standard form: **ax² + bx + c = 0**. To find the values of a, b, and c, we need to expand the equation and then compare it to the standard form.

### Expanding the Equation

Let's expand the equation (x+3)(x+4) using the FOIL method:

**F**irst: x * x = x²**O**uter: x * 4 = 4x**I**nner: 3 * x = 3x**L**ast: 3 * 4 = 12

Combining the terms, we get: x² + 4x + 3x + 12 = 0

Simplifying: **x² + 7x + 12 = 0**

### Identifying a, b, and c

Now, we can clearly see the values of a, b, and c:

**a = 1**(coefficient of x²)**b = 7**(coefficient of x)**c = 12**(constant term)

Therefore, the values of a, b, and c for the quadratic equation (x+3)(x+4)=0 are **a = 1, b = 7, and c = 12**.